Loss of Smell and Taste Among Healthcare Personnel Screened for Coronavirus 2019. (28th June 2020) - Kempker, Russell R; Kempker, Jordan A; Peters, Marcia; Rebolledo, Paulina A; Carroll, Kelley; Toomer, Linda; Wang, Yun F (Wayne); Ray, Susan M; Hunter, Mary
Abstract: Among 283 symptomatic healthcare personnel (HCP) tested for SARS-CoV-2, 51 (18%) were positive. Among those 51 HCP, self reported loss of smell and taste were present in 51% and 52.9%, respectively, with either present in 60.8%. These symptoms had high specificity (93% each, 96% for either) for a positive SARS-CoV-2 test.